THE UTILIZATION OF LEARNING MANAGEMENT SYSTEMS IN IMPROVING ACCESS TO AND QUALITY OF LEARNING IN ISLAMIC HIGHER EDUCATION INSTITUTIONS - Asrul Asrul; Mesiono Mesiono (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
This study aims to evaluate the utilization of Learning Management Systems (LMS) in improving access to and quality of learning in Islamic Higher Education Institutions in North Sumatra. The study is grounded in the increasing demand for digital transformation in higher education, where LMS is expected to support flexible learning, facilitate academic communication, provide structured learning materials, and strengthen learning evaluation. This research employed a qualitative field research approach involving Islamic higher education institutions in North Sumatra, including state and private Islamic higher education institutions. Data were collected through document studies, interviews, and in-depth semi-structured interviews with relevant institutional actors, lecturers, and students. The data were analyzed using inductive and interim analysis, while data validity was strengthened through prolonged engagement, triangulation, and member checking. The findings indicate that LMS utilization provides significant opportunities to expand learning access and improve the organization of academic activities. However, its implementation still faces several challenges, including uneven institutional readiness, limited infrastructure, varying levels of digital competence among lecturers and students, and inconsistent use of the platform. The study concludes that LMS should be developed not merely as a technological tool but as an integrated academic system for improving learning quality in Islamic higher education.